Understanding Archaeological Heritage Narratives From The Perspective Of Local Community Of Lenggong Valley - Balan, Yugeetha (2017)
This research explores the ways people understand and value archeological heritage based on the perspectives of Lenggong’s local community which is rich in archaeological finding and social context. The communication and interpretation of archaeological heritage in current times mostly focuses on the expert’s knowledge and much less on its social context. Therefore, this research’s focus on local perspectives is considered to be imperative in heritage discourses. The objective of this research is to explore meanings and values of archaeological heritage within a social context from the local community’s perspective that will contribute to sense of community. This research also acknowledges social dimensions of heritage and archaeological heritage through the narratives of the local community.